2020
DOI: 10.1093/cid/ciaa1533
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Voluntary Medical Male Circumcision for Human Immunodeficiency Virus Prevention in Rakai, Uganda

Abstract: Background The efficacy of voluntary male medical circumcision (VMMC) for HIV prevention in men was demonstrated in three randomized trials. This led to the adoption of VMMC as an integral component of the President’s Emergency Plan for AIDS Relief (PEPFAR) combination HIV prevention program in sub-Saharan Africa. However, evidence on the individual-level effectiveness of VMMC programs in real world, programmatic settings is limited. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
3
6
0
Order By: Relevance
“…Moreover, as also noted by the authors [9], observed major demographic and behavioral differences between genitally intact and circumcised men in the study left ample room for residual confounding.…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…Moreover, as also noted by the authors [9], observed major demographic and behavioral differences between genitally intact and circumcised men in the study left ample room for residual confounding.…”
Section: Introductionsupporting
confidence: 65%
“…As acknowledged by the authors, the new Uganda study failed to adjust for the impact of pre-exposure antiretroviral prophylaxis (PrEP), which is arguably the single most important biomedical determinant of HIV acquisition [ 11 – 13 ], and this omission may well have skewed the reported association of VMMC with HIV risk. Moreover, as also noted by the authors [ 9 ], observed major demographic and behavioral differences between genitally intact and circumcised men in the study left ample room for residual confounding.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…Evidence from three randomized controlled trials (RCTs) showed that MMC decreased heterosexual acquisition of HIV by 53 to 60%, herpes simplex virus type-2 (HSV-2) by 28 to 34% and genital ulcer disease among men [1][2][3][4]. Other studies [5][6][7][8], also found a protective effect of MMC against HIV infection and some sexually STIs acquired via heterosexual transmission.…”
Section: Introductionmentioning
confidence: 99%